Polishing cloth

The polishing cloth addresses the issue of reduced polishing rate due to resin impregnation by maintaining a moderate resin content and uniform void distribution, ensuring effective debris accommodation and sustained polishing performance.

JP2025061874AActive Publication Date: 2025-04-11NITTA DUPONT INC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
JP2025012020
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2019-12-27
Filing Date
2025-01-28
Publication Date
2025-04-11
Estimated Expiration
2040-10-05

AI Technical Summary

Technical Problem

Conventional polishing cloths with high resin impregnation to prevent end sagging often lead to clogged voids, reducing the polishing rate.

Method used

A polishing cloth with a nonwoven fabric and moderate resin impregnation, characterized by an apparent density of 0.30-0.50 g/cm³ and a standard deviation of the abundance ratio of the forming material of 21.7% or less, ensuring uniform void distribution and reduced clogging.

Benefits of technology

The polishing cloth maintains a high polishing rate even with moderate resin content, as the uniform void distribution minimizes clogging and maintains effective debris accommodation.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025061874000003
    Figure 2025061874000003
  • Figure 2025061874000004
    Figure 2025061874000004
  • Figure 2025061874000005
    Figure 2025061874000005
Patent Text Reader

Abstract

To provide a polishing cloth that hardly degrades its polishing rate even when a resin is properly included.SOLUTION: The polishing cloth includes, as a formation material, a nonwoven fabric and a resin impregnated in the nonwoven fabric and has an apparent density of 0.30-0.50 g / cm3, a standard deviation of an abundance ratio of the formation material of 21.7% or under, and a ventilation resistance value of 23 mmH2O or over.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a polishing cloth. [Background technology]

[0002] 2. Description of the Related Art Conventionally, a polishing cloth having a nonwoven fabric and a resin impregnated in the nonwoven fabric as a forming material has been used for polishing a workpiece such as a silicon wafer (for example, Patent Document 1).

[0003] Here, it is known that if the polishing cloth is too flexible, sagging occurs at the ends. Problems such as edge sagging can be avoided by increasing the amount of resin impregnation to harden the polishing cloth, but in that case, the presence ratio of the forming material of the polishing cloth increases. When polishing an object to be polished, the areas where no forming material is present (gaps) become spaces to accommodate shavings, so if the amount of resin impregnation is increased too much, the gaps become prone to clogging, and as a result, the polishing rate is likely to decrease. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] JP 2006-43811 A Summary of the Invention [Problem to be solved by the invention]

[0005] In view of the above problems, an object of the present invention is to provide a polishing cloth in which the polishing rate is unlikely to decrease even if the polishing cloth contains a moderate amount of resin. [Means for solving the problem]

[0006] The polishing cloth according to the present invention is a polishing cloth having a nonwoven fabric and a resin impregnated into the nonwoven fabric as a forming material, Apparent density: 0.30~0.50g / cm 3 and The standard deviation of the abundance ratio of the forming material is 21.7% or less, The airflow resistance is 23mmH2O or more.

[0007] In addition, since the standard deviation of the abundance ratio of the forming material in this polishing cloth is 21.7% or less, the ratio of voids is relatively uniform from the surface to the inside of the polishing cloth. And, in this polishing cloth, the voids are easily connected from the surface to the inside of the polishing cloth, so that even if some shavings are clogged in the voids, the polishing rate is unlikely to decrease. Effect of the Invention

[0008] As described above, according to the present invention, a polishing cloth in which the polishing rate is unlikely to decrease even if a moderate amount of resin is contained can be provided. [Brief description of the drawings]

[0009] [Figure 1] Schematic diagram of the device used to measure airflow resistance (APR). [Diagram 2] arithmetic mean values ​​of the abundance ratios of forming materials in each cross section of the polishing pads of Examples 1-1, 2-1, and Comparative Example 1-1. [Diagram 3] arithmetic mean values ​​of the abundance ratio of forming materials in each cross section of the polishing pads of Examples 5-1, 6-1, and Comparative Example 2-1. [Figure 4] 1 shows the polishing rate when a wafer was polished using the polishing cloths of Examples 1-1, 2-1, 3, and 4 and Comparative Example 1-1. [Diagram 5] 4 shows the polishing rates when a wafer was polished using the polishing cloths of Examples 5-1, 6-1, and Comparative Example 2-1. [Figure 6] The reduction rate of the polishing rate when a wafer is polished using the polishing cloths of Examples 1-1, 2-1, 3, and 4 and Comparative Example 1-1. [Figure 7] The reduction rate of the polishing rate when a wafer is polished using the polishing cloths of Examples 5-1, 6-1, and Comparative Example 2-1. [Figure 8] SEM image (50x) of the surface of the polishing cloth of Example 1-1. [Figure 9]SEM image (50x) of the cross section of the polishing cloth of Example 1-1. [Figure 10] SEM image (50x) of the surface of the polishing cloth of Comparative Example 1-1. [Figure 11] SEM image (50x) of the cross section of the polishing cloth of Comparative Example 1-1. [Figure 12] SEM image (50x) of the surface of the polishing cloth of Example 5-1. [Figure 13] SEM image (50x) of the cross section of the polishing cloth of Example 5-1. [Figure 14] SEM image (50x) of the surface of the polishing cloth of Comparative Example 2-1. [Figure 15] SEM image (50x) of the cross section of the polishing cloth of Comparative Example 2-1. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0010] Hereinafter, an embodiment of the present invention will be described with reference to the accompanying drawings.

[0011] The polishing cloth according to this embodiment includes, as its forming materials, a nonwoven fabric and a resin impregnated into the nonwoven fabric. In addition, the polishing cloth according to this embodiment has an apparent density of 0.30 to 0.50 g / cm 3 It is important that the standard deviation of the abundance ratio of the forming material is 21.7% or less. In the polishing cloth according to this embodiment, the average abundance ratio of the forming material is preferably 22 to 45%, more preferably 30 to 45%, and further preferably 35 to 45%.

[0012] The apparent density is 0.30 to 0.50 g / cm 3 and preferably 0.35 to 0.50 g / cm 3 , more preferably 0.35 to 0.45 g / cm 3 It is. The apparent density can be measured based on JIS K7222:2005.

[0013] The "average value of the abundance ratio of the forming material" and the "standard deviation of the abundance ratio of the forming material" can be determined as follows. That is, two measurement surfaces of 2000 μm x 2000 μm are photographed (the two measurement surfaces are different locations) for a slice surface parallel to the surface of the abrasive cloth every 100 μm from the front to the back surface, and 168 surfaces of 100 μm x 100 μm are extracted from each measurement surface, and the abundance ratio of the forming material in each of the extracted 100 μm x 100 μm surfaces is measured. The arithmetic mean value of the measured abundance ratios of the forming materials is defined as the "average abundance ratio of the forming materials," and the standard deviation of the measured abundance ratios of the forming materials is defined as the "standard deviation of the abundance ratios of the forming materials." The abundance ratio of the forming material in each 100 μm × 100 μm surface means the ratio of the area of ​​the portion where the forming material is present when the entire area of ​​each 100 μm × 100 μm surface is taken as 100%. For example, when observing a sliced ​​surface having a size of 100 μm to 1200 μm from the front surface to the back surface, the abundance ratio of the forming material of a surface of 100 μm×100 μm (168×12×2) is measured.

[0014] In the measurement, the polishing cloth is photographed by CT-scan. Specifically, two 2000 μm x 2000 μm measurement surfaces are photographed (the two measurement surfaces are different locations) for a slice surface parallel to the surface of the abrasive cloth every 100 μm from the front to the back, and 168 100 μm x 100 μm surfaces are extracted from each measurement surface. The images of each 100 μm x 100 μm surface are then subjected to a binarization process to classify them into voids and non-void areas (areas where the forming material is present), thereby measuring the presence ratio (area ratio) of the forming material on the observation surface. As the CT device, a three-dimensional measuring X-ray CT device (TDM1000H-1) manufactured by Yamato Scientific Co., Ltd. can be used. As the CT image processing software, the image processing software VGStudio Max 2.1 manufactured by Japan Visual Science Volume Graphics Co., Ltd. can be used. Furthermore, as image analysis software for calculating the abundance ratio (area ratio) of the forming materials, ImageJ (Rasband, WS, US National Institutes of Health, Bethesda, Maryland, USA) can be used.

[0015] For example, the abundance ratio (area ratio) of the forming material is measured under the following conditions.

[0016] In the above measurement, the measurement surface of the polishing cloth is continuously measured with the following field of view size. Field of view size (length x width x height): 2,000μm x 2,000μm x full thickness The measurement conditions are as follows: Views per rotation: 1500 Frames / Views: 10 X-ray tube voltage [KV]: 28.000 Enlarged axis position [mm]: 7.416 Reconstruction pixel size X (mm): 0.003880 Reconstruction pixel size Y [mm]: 0.003880 Reconstruction pixel size Z (mm): 0.003880

[0017] The binarization process for classifying each measurement surface into voids and non-void portions (portions where forming material exists) is as follows. In the binarization process, the contrast of the image of the measurement surface is adjusted in VGStudio Max in order to classify the area into voids and non-void areas (areas where the forming material is present). Contrast adjustment is done in Ramp mode. The contrast is adjusted so that the difference between the voids and the areas other than the voids (areas where the forming material exists) becomes clear. In VGStudio Max, contrast adjustment is listed as "opacity adjustment." Specifically, in the VGStudio Max opacity adjustment screen, the lower limit of the gray value is set to the peak, and then the upper limit of the gray value is set to the range of "peak value of the peak + 100 ± 5." Note that the light transmittance differs depending on the material, so the contrast adjustment range is not necessarily limited to this.

[0018] For the contrast-adjusted 2D image, an image of the measurement surface is acquired.

[0019] Next, the abundance ratio of the forming material is measured using ImageJ for the acquired image of the measurement surface. Here, the measurement range in ImageJ is 1200μm×1400μm. The upper left corner of the image data is set as (x,y)=(0pix,0pix) position, and the measurement range is 312pix (=1201.2μm) horizontally and 364pix (=1401.4μm) vertically from the (132,22) position. After that, the image type is converted from RGB color to 8bit, and the image is binarized. Under these binarization conditions, the range of gradation from "129" to "255" corresponds to the part where the forming material exists. The image size of this image data is reduced to 12pix horizontally × 14pix vertically. 1pix×1pix of this reduced image becomes a surface of 100μm×100μm. This operation is performed every 100μm in the thickness direction from the front to the back. In the binarization process in ImageJ, the areas with a gradation range of "129" to "255" are regarded as areas other than voids (areas where forming material exists).

[0020] The compressibility of the polishing cloth according to this embodiment is preferably 5% or less, and more preferably 3.5% or less. The compression ratio can be calculated by the following method. That is, a compression elasticity tester (indenter area: 50 mm) according to JIS L1096:2010 was used. 2 ) was applied to the polishing cloth with a pressure of 300gf / cm 2 After pressing the polishing cloth in the thickness direction with a pressure of 1800 gf / cm for 60 seconds, the thickness T1 of the polishing cloth is measured. Then, the pressure of 1800 gf / cm is applied to the polishing cloth with the indenter. 2After pressing the polishing pad in the thickness direction at a pressure of 1000 MPa and holding the pressure for 60 seconds, the thickness T2 of the polishing pad is measured, and the compression ratio can be calculated using the following formula. Compression ratio = (T1-T2)×100 / T1

[0021] The hardness (Asker-C) of the polishing cloth according to this embodiment is preferably 80 or more, and more preferably 85-95. The polishing cloth according to this embodiment has an advantage that the edge sagging of the workpiece (e.g., a wafer, etc.) is unlikely to occur due to the hardness of 80 or more. In addition, the polishing cloth according to this embodiment has an advantage that the workpiece is unlikely to have defects (e.g., scratches, etc.) due to the hardness of 95 or less. The hardness is a value measured according to the standard SRIS0101 (Japan Rubber Association Standard). The Asker-C hardness is measured on the one surface. In other words, the hardness is measured on the polished surface.

[0022] The thickness of the polishing cloth according to this embodiment is preferably 0.8 to 2.0 mm, and more preferably 1.0 to 1.5 mm. The polishing cloth according to the present embodiment has a thickness of 0.8 mm or more, which has the advantage that it is easy to reduce the adverse effect on the polishing performance caused by the state of the polishing machine platen, and also has the advantage that, for example, it is easy to stably flatten the polished object. Furthermore, the polishing cloth according to this embodiment has a thickness of 2.0 mm or less, which reduces the amount of deformation of the polishing cloth during polishing, and as a result has the advantage that sagging of the edges of the workpiece is less likely to occur.

[0023] Examples of the fibers constituting the nonwoven fabric include polyester fibers and nylon fibers. The nonwoven fabric preferably has a basis weight of 200 to 600 g / m 2 It is. The polishing cloth according to this embodiment has a nonwoven fabric weight of 200 g / m 2By being equal to or greater than this, the hardness is easily increased, and as a result, there is an advantage that the edge sagging of the workpiece to be polished is less likely to occur. 2 As a result, the polishing cloth according to the present embodiment has an advantage that such a configuration makes it easier to suppress fluctuations in polishing performance due to clogging of the voids by polishing debris and the like.

[0024] The resin may be a urethane resin.

[0025] An example of an object to be polished with the polishing cloth according to this embodiment is a silicon wafer.

[0026] The polishing cloth according to this embodiment is configured as described above. Next, a method for manufacturing the polishing cloth according to this embodiment will be described.

[0027] The manufacturing method of the polishing cloth according to this embodiment will be described below by taking as an example a method of performing a two-stage impregnation process in which a nonwoven fabric is wet-impregnated with a urethane resin and then dry-impregnated with the urethane resin.

[0028] In the wet impregnation, a urethane resin is dissolved in a water-soluble organic solvent to obtain a first impregnation liquid. Examples of the water-soluble organic solvent include dimethylformamide, dimethylsulfoxide, tetrahydrofuran, and dimethylacetamide. The first impregnation liquid may contain a filler. Examples of the filler include carbon black. The first impregnation liquid may contain a dispersion stabilizer. Examples of the dispersion stabilizer include a surfactant. Next, the nonwoven fabric is immersed in the first impregnation liquid, and the nonwoven fabric that has been immersed in the first impregnation liquid is then immersed in water, whereby the water-soluble organic solvent in the first impregnation liquid attached to the nonwoven fabric is replaced with water, the urethane resin solidifies, and the urethane resin adheres to the surface of the nonwoven fabric.

[0029] In the dry impregnation, a prepolymer having an isocyanate group as a terminal group, a curing agent which is an organic compound having active hydrogen, and an organic solvent are mixed to obtain a second impregnation liquid. Examples of the organic solvent include methyl ethyl ketone, acetone, alcohol, and ethyl acetate. The wet-impregnated nonwoven fabric is then immersed in a second impregnation liquid, and the nonwoven fabric immersed in the second impregnation liquid is heated in a drying oven, whereby the organic solvent is evaporated and the prepolymer and the curing agent undergo a curing reaction to form a urethane resin, resulting in further urethane resin adhering to the surface of the nonwoven fabric.

[0030] The polishing cloth according to this embodiment is configured as described above and has the following advantages.

[0031] That is, the polishing cloth according to this embodiment is a polishing cloth having a nonwoven fabric and a resin impregnated in the nonwoven fabric as a forming material. Also, the polishing cloth according to this embodiment has an apparent density of 0.30 to 0.50 g / cm 3 and the standard deviation of the abundance ratio of the forming material is 21.7% or less.

[0032] Such a polishing cloth has an apparent density of 0.50 g / cm 3 By keeping the thickness of the polishing plate at or below this value, the polishing rate is less likely to decrease even if the polishing plate is clogged with some shavings, since the polishing plate is more likely to have many voids. In addition, the polishing cloth according to this embodiment has a standard deviation of the abundance ratio of the forming material of 21.7% or less, so that the ratio of voids is relatively uniform from the surface to the inside of the polishing cloth. And, in this polishing cloth, the voids are easily connected from the surface to the inside of the polishing cloth, so that even if some shavings are clogged in the voids, the polishing rate is unlikely to decrease. Furthermore, the apparent density of the polishing cloth is 0.30 g / cm 3 As a result of the above, the number of locations where the material is present can be increased, resulting in a high hardness, and as a result, drooping at the ends is less likely to occur.

[0033] The polishing cloth according to the present invention is not limited to the above embodiment. The polishing cloth according to the present invention is also not limited by the above-mentioned action and effect. The polishing cloth according to the present invention can be modified in various ways without departing from the gist of the present invention.

[0034] For example, in this embodiment, the polishing cloth is obtained by a method of carrying out a two-stage impregnation process, but the polishing cloth may be obtained by only wet impregnation or dry impregnation. EXAMPLES

[0035] Next, the present invention will be described more specifically with reference to examples and comparative examples.

[0036] Polishing cloths of the examples were produced, the physical properties of which are shown in Tables 1 and 2. Polishing cloths (commercially available products) whose physical properties are shown in Tables 1 and 2 were prepared. The hardness, compressibility, apparent density, average value of the abundance ratio of the forming material, and standard deviation of the abundance ratio of the forming material were measured by the methods described above. The air flow resistance (hereinafter referred to as "APR") means the pressure loss when air is passed through the polishing cloth in the thickness direction using the device shown in Figure 1 (air flow rate: 30 L / min, air pressure: 100 Pa).

[0037] FIG. 2 shows the arithmetic mean values ​​of the abundance ratios of the forming materials in each cross section of the polishing pads of Examples 1-1, 2-1 and Comparative Example 1-1. FIG. 3 also shows the arithmetic mean values ​​of the abundance ratios of the forming materials in each cross section of the polishing pads of Examples 5-1, 6-1 and Comparative Example 2-1.

[0038] Density is 0.4g / cm 3 and polishing pads with a density of 0.4 g / cm 3 The following polishing pads were evaluated under different conditions as follows. 1) Density 0.4g / cm 3 Polishing pads exceeding: Comparative Examples 1-1 to 1-3, Examples 1-1 to 1-3, Examples 2-1 to 2-3, Example 3, Example 4 The polishing rate was measured when a wafer was polished using the polishing pad. The measurement was carried out after the polishing cloth was set in the apparatus and after dressing treatment was carried out under running water for 5 minutes under the following conditions before polishing. Dresser: Kinik pellet type dresser #150 (12 pellets with a diameter of 20 mm placed under the plate) Load: 18.7kg Rotational speed: Head / Platen=100 / 115rpm 2) Density 0.4g / cm 3 The following polishing pads: Comparative Examples 2-1 to 2-3, Examples 5-1 to 5-3, Examples 6-1 to 6-3 The density was 0.4 g / cm except that the polishing rate was measured without dressing treatment. 3 The polishing pad was evaluated in the same manner as above.

[0039] The polishing conditions for measuring the polishing rate are shown below. The weight of the wafer was measured for each polishing (for each run), and the removal rate (RR) was calculated from the difference between the weight of the wafer before and after polishing. Some of the results are shown in Figures 4 and 5. The "polishing rate decrease rate" was calculated using the following formula. The results are shown in Tables 1 and 2 and Figures 6 and 7. Polishing rate decrease rate (%) = (maximum polishing rate - minimum polishing rate) / maximum polishing rate × 100(%) In addition, no treatments to remove clogging (e.g., dressing, brushing, or HPMJ (high pressure microjet cleaning) treatments) were performed between runs. Polishing time: 60 minutes for the first run only, 40 minutes from the second run Run: 7 times (apparent density 0.40g / cm 3 For the following polishing pads, use 6 times) Polishing machine: Strasbaugh 6CA Wafer: 8”(P-) Polishing fluid: The addition rate of each polishing fluid to DIW (pure water) was 7.14%. ·Density 0.4g / cm 3 Super polishing cloth: solution with solid content (115℃) 36.6%, average particle size 108nm, pH=11.3 ·Density 0.4g / cm 3 The following abrasive cloths: NP6503 (manufactured by Nitta Haas Corporation) Polishing fluid flow rate: 300mL / min Polishing time: 40min / run 8 to 15 show SEM images of the surfaces and cross sections of the polishing pads of Example 1-1, Comparative Example 1-1, Example 5-1, and Comparative Example 2-1.

[0040] [Table 1]

[0041] [Table 2]

[0042] As shown in FIGS. 6 and 7 and Tables 1 and 2, the polishing cloths of the Examples had a smaller decrease in the polishing rate than the Comparative Examples.

Claims

1. A polishing cloth comprising a nonwoven fabric and a resin impregnated in the nonwoven fabric as a forming material, Apparent density: 0.30 to 0.50 g / cm 3 and The standard deviation of the abundance ratio of the forming material is 21.7% or less, Air flow resistance is 23mmH 2 A polishing cloth having a polishing ability of O or higher.

2. 2. The polishing cloth according to claim 1, which has a compressibility of 5% or less.

3. 3. The polishing cloth according to claim 1, wherein the average content of said forming material is 22 to 45%.

Citation Information

Patent Citations

  • Polishing pad

    JP2017013149A

  • Polishing cloth

    JP2019025549A

  • Polishing cloth

    JP2006043811A